2021
DOI: 10.1177/00208523211003122
|View full text |Cite
|
Sign up to set email alerts
|

From the participatory turn of administrations to the bureaucratisation of participatory democracy: study based on the French case

Abstract: This article sets out to contribute to the debate on the participatory turn of public action and the administration by studying the profile and work of civil servants dedicated to citizen participation within French local administrations. Counter to the rhetoric advocating the participatory modernisation of the administration, an analysis of the day-to-day work of civil servants in charge of participation makes it possible to grasp the dynamics behind the bureaucratisation of citizen participation. Without act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Sayfullayeva (2021) presents opportunities for teaching disciplines using innovative technologies in technical institutions, examining the concept of innovation in education and its impact on teacher competence and student learning activities [39]. This analyses regarding the fact that the context of the location should be taken into account are crucial for deciding which mound is hindering the growth and whether governing bodies and companies are willing to be engaged [17]. The accountability measures must be implemented as a policy priority, allowing the students to acquire the skills via the knowledge gained in their internships or apprenticeships.…”
Section: Incentivizing School-business Collaborationsmentioning
confidence: 99%
“…Sayfullayeva (2021) presents opportunities for teaching disciplines using innovative technologies in technical institutions, examining the concept of innovation in education and its impact on teacher competence and student learning activities [39]. This analyses regarding the fact that the context of the location should be taken into account are crucial for deciding which mound is hindering the growth and whether governing bodies and companies are willing to be engaged [17]. The accountability measures must be implemented as a policy priority, allowing the students to acquire the skills via the knowledge gained in their internships or apprenticeships.…”
Section: Incentivizing School-business Collaborationsmentioning
confidence: 99%
“…(2020) summarize, dissatisfaction with current representative democracy increases citizens' desire for more participation opportunities, regardless of what those are. It is not equally clear how policymakers interpret the push for more citizen participation, which they have likely experienced through public discourse, empowerment initiatives and the consolidation of populist parties (see e.g., Fernández‐Martínez et al., 2020 and Gourgues et al., 2021 for discussion). While the participatory ethos aligns with the hopes of many citizen groups, unifying “strange bedfellows” like radical democrats and populists, the situation probably seems more complex in general from the policymakers' viewpoint and their reactions are likely to vary across different elite groups.…”
Section: Attitudes Towards Citizen Engagementmentioning
confidence: 99%
“…As many studies have shown, participation is a medium better depicted on a continuum. Generally celebrated by public actors as inherently positive, participatory processes have nevertheless been criticized for their potential to become increasingly ritualistic and bureaucratic, or for having conflicting implications-such as in the case of voluntary work (Bonet & Négrier, 2018;Brook, O'Brien & Taylor, 2021;Marx, 2019;Gourgues et al, 2022). In an empirical study of the participatory turn of public administration in France, Gourgues et al have shown a proliferation of "participation professionals," such as facilitators, community consultants, and policy officers in the public sector, whose jobs have come to amount to "little more than the incessant production of events (meetings, encounters, sessions, and committees)," or the endless generation of records of such participatory activities (2022, p.1148).…”
Section: Introductionmentioning
confidence: 99%